Environmental and economic comparison of wire and swarf in a novel additive manufacturing technique for aerospace applications - Karadimas, Georgios; Thayapararajah, Samniroshan; Pagone, Emanuele; Salonitis, Konstantinos; Williams, Stewart W. (Springer, 2026)
In the context of sustainable manufacturingSustainable manufacturing, the choice of materials and processes significantly impacts the environmental footprint and overall costs of additive manufacturingAdditive manufacturing (AM). This study investigates the use of wire versus swarfSwarf feedstock as feedstocks in a novel additive manufacturingAdditive manufacturing technique process and compares these methods with Wire Arc Additive ManufacturingAdditive manufacturing (WAAM). Specifically, the carbonCarbon footprint (CO2 emissions), energyEnergy consumption, and cost implications of each approach are evaluated. The findings reveal that, while wire-based methods are commonly employed for their precision and quality, swarf recycled from manufacturing waste offers substantial environmental benefits by reducing energyEnergy consumption and lowering carbonCarbon emissions. Moreover, the cost comparison shows that swarf can reduce overall production costs, providing a more cost-effective solution, especially in high-volume aerospace applications. This work highlights the potential of integrating swarf into WAAM processes as a sustainable alternative, offering insights into optimizing both environmental performance and economic viability in AM. The results are expected to contribute to the advancement of more sustainable and economically viable additive manufacturingAdditive manufacturing strategies.
Keywords: 41 Environmental Sciences; 4014 Manufacturing Engineering; 40 Engineering; 4104 Environmental Management; 12 Responsible Consumption and Production; Sustainable Manufacturing; Additive Manufacturing; Swarf Feedstock; Aerospace Manufacturing; Environmental and Economic Impact